Catalysts based on nickel salt heteropolytungstates for selective oxidation of diphenyl sulfide - Muñoz, Mercedes (2023)
Nickel salts of Keggin heteropolytungstates with the general formula NixAyW12−yO39or40 (A = Si/P) were synthesized and studied as bulk catalytic materials or supported ones by deposition on modified and functionalized clay minerals (pillared layered clay and porous clay heterostructure). Characterizations by Raman, 31P and 29Si-NMR, and ESEM-EDS techniques showed that pure and supported systems preserved the Ni/W ratio and the expected structural properties of heteropolyanions. These materials were evaluated as catalysts in the selective oxidation of sulfides to sulfoxides or sulfones, using aqueous hydrogen peroxide and mild reaction conditions. The bulk materials, with a higher content of Ni, displayed a remarkable catalytic behavior in the oxidation of diphenyl sulfide (Ni3PW11NiO40H, 90% conversion in 15min at 75°C, 100% sulfone selectivityin 3 h). Supported catalysts, particularly the non-functionalized PCH (Ni2SW12O40/PCH), showed excellent activity, with also being selective in the oxidation of sulfide to sulfoxide (87% conversion, 88.9% sulfoxide selectivity). The reuse of these materials was studied in the optimum reaction conditions, resulting in similar activity and selectivity.